Poverty Dynamics the Structurally and Stochastically Poor in Vietnam - Nguyễn, Việt Cường (H. : ĐHQGHN, 2017)
This paper aims to measure poverty dynamics in Vietnam using the most recent Vietnam Household Living Standard Survey (VHLSS) from 2010. Since there are no panel data between the 2010 VHLSS and the previous studies, this study uses the asset approach to estimate the proportion of structurally and stochastically poor. It is found that the proportion of structurally and stochastically poor is 11.1 percent and 9.6 percent, respectively. Nearly half of the poor are the stochastically poor. The proportion of stochastically non-poor, who are non-poor but vulnerable to poverty, is small, at around 3.7 percent.